Preventing Child Marriage: The Role of Strategic Actors in South Kalimantan - Vinita Susanti; Reni Kartikawati; Irwan M Hidayana; Ida Ruwaida; Lusiana Rumintang (Universitas Andalas, 2021)
South Kalimantan Province is the province with the highest number of child marriage cases, according to data from the Central Statistics Agency (BPS) in 2017 and 2019. This has resulted in various negative impacts, one of which is the high maternal mortality rate, as well as the low human development index (HDI) in the province, which is placed at the 22nd position from 34 provinces in Indonesia. This paper aims to examine various strategic actors who can prevent and reduce the practice of child marriage in South Kalimantan Province in three levels of analysis: the macro, mezzo, and micro levels. This paper seeks the relationship between the three aspects of structure, culture, and social processes at the three macro, mezzo, and micro levels, as the concept of analysis used to prevent child marriage practices from a child protection perspective and SRHR issues. This study uses a qualitative approach through in-depth interview methods to key policy makers and is supported by focus group discussions (FGD) to participants in discussions from various backgrounds, both government agencies, and non-governmental organizations concerned with the issue of child and women's protection in South Kalimantan Province.